Synthesis of Organic Material-Derived Carbon Quantum Dots: Nitrogen Doping and Fluorescence Modulation for Metal Ion Sensing (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
Nitrogen-doped carbon quantum dots (N-CDs) were synthesized from Terung Dayak (Solanum ferox) using a microwave-assisted method. This study investigated their optical properties and fluorescence modulation in the presence of metal ions. The synthesis involved citric acid as the carbon precursor and urea as the nitrogen dopant, leading to well-dispersed N-CDs with enhanced fluorescence characteristics. UV-Vis and fluorescence spectroscopy confirmed the successful incorporation of nitrogen, which resulted in a redshifted emission peak and improved fluorescence intensity compared to undoped CDs. The band gap analysis using Tauc plots indicated an increase in energy gap upon nitrogen doping, suggesting modifications in the electronic structure. Furthermore, fluorescence response experiments demonstrated that the presence of Pb²⁺ ions significantly enhanced the emission intensity, indicating potential applications in metal ion sensing. The results highlight the influence of nitrogen doping on the optical properties of carbon quantum dots and their promising use in fluorescence-based sensing applications.